Development Of Hygienic Urinal Device Using Integrated Approach - Arep @ Ariff, Hambali; Abdul Halim, Muhammad Firdaus; Jaafar, Roshidah; Mohamad, Effendi; Hambali, Ruzy Haryati (World Academy of Research in Science and Engineering, 2020)
This research presented the process of improving the existing hygienic urinal device using the integrated approach. Thus, various design activities have been involved in designing and fabricating the proposed product. The research aims to design and fabricate a new hygienic urinal device for solving the person who has difficulty accessing the toilet. The design process is based on the integrated method or Pugh's approach which includes various design activities such as market investigation, concept generation, concept selection, concept development and rapid prototyping concept. Investigating the existing similar product was carried out to ideate and generate the idea to improve the previous product. Analytical Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) were implemented to decide the best design concept during the selection process at the conceptual design stage. the best selected proposed design was fabricated using a 3D printer. The results showed that the improvement of the proposed new design which is 41% in terms of the number of parts, 2.05% in terms of fabrication time, 40% in terms of the number of operations, 11.8% in terms of weight reduction and 11.91% in terms of material cost reduction. This is showed that the proposed new design of the hygienic urinal device is much better compared to the existing design